Phyllodes Tumor: A Rare Case with Cervical Vertebral Metastasis - Kutty, Shankar Ayyappan; Rajeevan, Lilly (Indian Journal of Neurosurgery, 2015)
Background Phyllodes tumor or cystosarcoma phyllodes is a rare tumor that accounts for less than 1% of breast lesions. Incidence of these lesions metastasizing to distant sites is very low and only a few cases of metastases to central nervous system have been reported. The management of a case with cervical spine metastasis is described and current literature has been reviewed.Case Description A 32-year-old woman who underwent excision of cystosarcoma phyllodes of the right breast presented with neck pain. Evaluation showed destruction of the C3–C4 vertebrae. Anterior decompression with anterior and posterior fusion was done, followed by radiotherapy.Conclusion Spinal metastasis from cystosarcoma phyllodes is extremely rare, but should be kept in mind when a patient presents with symptoms suggestive of a spinal problem. Surgical management of these tumors may enhance the quality of life of these patients.
Keywords: cystosarcoma phyllodes; cervical spine; metastasis; vertebrae